2006
DOI: 10.1016/j.immuni.2006.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Human 6-Sulfo LacNAc-Expressing Dendritic Cells Are Principal Producers of Early Interleukin-12 and Are Controlled by Erythrocytes

Abstract: Early and high-level production of IL-12 is crucial for effective immune responses against pathogens. Up until now, the cells providing this initial IL-12 have remained elusive. Here we show that a subset of human blood dendritic cells (DC) is the principal and primary source of IL-12p70 when blood leukocytes are stimulated with the TLR4-ligand LPS or with CD40-ligand. These so-called slanDC are characterized by the 6-sulfo LacNAc modification of PSGL-1, which is identified by the mAb M-DC8. The IL-12 response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
255
1
8

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 171 publications
(273 citation statements)
references
References 39 publications
9
255
1
8
Order By: Relevance
“…Which cell type expressing CD47 precisely interacts with SIRP-␣ on DC and under which conditions does it happen in vivo? Schakel et al (50) recently demonstrated that IL-12 p70 secretion is abundantly secreted in response to TLR ligands by a blood DC subset provided the contact between CD47 on erythrocytes and SIRP-␣ on DC is interrupted. Also, SIRP-␣ is engaged by CD47-expressing live but not apoptotic cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…Which cell type expressing CD47 precisely interacts with SIRP-␣ on DC and under which conditions does it happen in vivo? Schakel et al (50) recently demonstrated that IL-12 p70 secretion is abundantly secreted in response to TLR ligands by a blood DC subset provided the contact between CD47 on erythrocytes and SIRP-␣ on DC is interrupted. Also, SIRP-␣ is engaged by CD47-expressing live but not apoptotic cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…12). Functionally, slanDCs stand out for their remarkable capacity to produce tumour necrosis factor alpha (TNFa) and IL-12p70 upon stimulation with discrete toll-like receptor ligands 13,14 . In addition, they are potent inducers of primary antigen-specific T-cell responses in vitro 11 , and show a superior programming of Th1/Th17 cell polarization as compared with classical CD1c þ DCs 14 .…”
mentioning
confidence: 99%
“…Recently, we defined 6-sulfo LacNAc (slan)DCs (formerly termed M-DC8 þ DCs) as a major subpopulation of proinflammatory myeloid human blood DCs, which mainly differ from other blood DC subsets by their selective phenotype (6- 5,6 Functional data revealed that slanDCs can mediate tumor-directed cytotoxicity and efficiently activate tumor-reactive NK cells and CD8 þ CTLs. 7 To get novel insights into the impact of primary human AML cells on native human DCs, we investigated the capacity of AML cells to modulate the secretion of TNF-a and IL-12 by slanDCs.…”
mentioning
confidence: 99%
“…5,7 In addition, we have shown that activated slanDCs are principal producers of IL-12, which favors the differentiation of naive CD4 þ T cells into Th1 cells and is important in NK cell activation. 6,8 Blood samples were obtained from healthy donors with informed consent. Immunomagnetic isolation of slanDCs (purity: 490%) from peripheral blood mononuclear cells was performed as previously described.…”
mentioning
confidence: 99%
See 1 more Smart Citation